Expression and activity evaluation of reteplase in Escherichia coli TOP10 - Shafiee, Fatemeh; Moazen, Fatemeh; Rabbani, Mahammad; Mir Mohammad Sadeghi, Hamid (Archives of Advances in Biosciences, 2015)
Reteplase is a part of tissue Plasminogen Activator (t-PA) used for theremoval of thrombi in blood vessels. In the present study we express the reteplase genein Escherichia coli TOP10 and then its thrombolytic activity was measured. The recombinant plasmid pBADgIIIA was transformed into the competent Escherichia coli TOP10and then transformed bacteria was seeded into bioreactor containing 1.5 L LB medium and induced by 0.02% L-Arabinoseat 37°C, pH 7, and 180 rpm until OD 600 of 0.6 was reached.Samples were analyzed by SDS-PAGE and western blotting andthe expression of reteplase was examined. Finally the activity of this recombinant protein was evaluated using Chromogenic Activity Assay Kit. The presence of reteplase in transformed Escherichia coli TOP10 wasexamined by western blotting which revealed that the target protein in form inclusion body was expressed as a unique band at39 and the refolded reteplase was 66KDa. The amount of protein produced was 90.5µg/mL and its activity was determined as 0.8 units. In this study, the expression of reteplase in Escherichia coli TOP10 wasscaled up under optimum condition. Furthermore we earned reteplase with partially suitable thrombolytic activity.